Aging-resistant basalt fiber composite material and preparation method thereof
Patent Information
- Application Number
- CN202611203974.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-11-03
AI Technical Summary
Basalt fiber composites are prone to interfacial debonding and delamination defects in complex environments such as humid heat, ultraviolet radiation, and thermo-oxidative stress, leading to a decline in mechanical properties. Existing modification methods cannot effectively quench aging free radicals and have poor interfacial compatibility, making it difficult to achieve a synergistic improvement in aging resistance and mechanical strength.
Phytic acid, zirconium oxychloride, cerium nitrate, γ-glycidyl etheroxypropyltrimethoxysilane, and epoxy-modified polyphosphonate oligomers are used to form a dense barrier layer, a dynamic free radical trapping layer, and a chemically bonded layer through a multi-step process of low-temperature plasma activation, two-step in-situ coordination deposition, silane gradient grafting, and co-curing with the matrix. This process synergistically improves the material's aging resistance and mechanical properties.
The material achieves excellent aging resistance and improved interlaminar shear strength by using a zirconium phytate hybrid layer to lock ion dissolution channels, a cerium-doped layer to dynamically capture free radicals, a silane gradient layer to buffer stress, and an epoxy-modified polyphosphonate to enhance crosslinking density.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of fiber composite materials technology, specifically to an aging-resistant basalt fiber composite material and its preparation method. Background Technology
[0002] Basalt fiber composites, with their advantages of high cost-effectiveness, excellent mechanical properties, and heat and corrosion resistance, are widely used in rail transportation, wind power equipment, building reinforcement, and aerospace. However, the surface of basalt fibers is rich in active metal ions such as calcium, iron, and magnesium, which are prone to continuous dissolution under complex service environments of humidity, heat, ultraviolet radiation, and thermo-oxidation, catalyzing the hydrolytic degradation of the resin matrix. Simultaneously, moisture easily penetrates the fiber-resin interface, causing interfacial debonding and delamination defects. Traditional surface modification methods are mostly single-coating protection, achieving only simple physical barriers and lacking dynamic anti-aging mechanisms. They cannot effectively quench aging free radicals, leading to a significant decline in mechanical properties after long-term service. Furthermore, conventional modified layers have poor compatibility with the matrix, resulting in significant interfacial stress concentration and the formation of weak interfacial layers, making it difficult to simultaneously improve the composite material's aging resistance and mechanical strength. Addressing the technical pain points of poor interfacial stability, weak aging resistance, and insufficient overall service performance of existing basalt fiber composites, the development of high-strength, aging-resistant basalt fiber composites with multi-mechanism synergistic modification has significant engineering application value. Summary of the Invention
[0003] The purpose of this invention is to provide an aging-resistant basalt fiber composite material and its preparation method, so as to solve the problems existing in the prior art.
[0004] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for preparing an aging-resistant basalt fiber composite material, comprising the following steps: (1) Mix phytic acid solution and deionized water at a mass ratio of 1~2:30, stir at room temperature for 15 min, and add buffer solution to adjust pH to 4.0~4.5 to obtain a mixed solution; mix zirconium oxychloride octahydrate and deionized water at a mass ratio of 1~2:10, stir until clear, and slowly add to the above mixed solution while stirring continuously. Continue stirring for 30 min to obtain a precursor sol. Completely immerse the basalt fiber plain weave fabric that has been pretreated by plasma in the precursor solution, soak at 40℃ for 1~3 h, turn the fiber once every 20 min, take out the fiber, wash, and dry at 80℃ for 30 min to obtain intermediate product A; (2) Add cerium nitrate hexahydrate to anhydrous ethanol and stir at 25°C for 20 min to prepare a 0.01 mol / L cerium nitrate ethanol solution; completely immerse intermediate product A in the solution and soak at 25°C for 1-2 h, remove the fiber, wash it, and dry it at 80°C for 1 h to obtain intermediate product B; completely immerse intermediate product B in silane coupling agent hydrolysate and soak at 25°C for 30 min, remove the fiber, wash it, and pre-cur it at 110°C for 15 min to obtain intermediate product C; (3) Mix 90-110 parts by weight of epoxy resin and 7-9 parts by weight of epoxy-modified polyphosphonate oligomer, heat to 60°C and premix for 20 min, cool to room temperature, add 80-90 parts by weight of curing agent and 1-2 parts by weight of accelerator, continue to stir at a constant speed for 15 min at room temperature, and degas under vacuum for 15 min to obtain resin solution; lay 8 layers of intermediate product C in orthogonal layup sequence, vacuum and pressure test for leaks, preheat to 60°C and then introduce resin solution for gradient curing, cool to room temperature, and place in a room temperature desiccator for curing for 7 days to obtain aging resistant basalt fiber composite material.
[0005] Furthermore, the phytic acid solution in step (1) is a 50wt% phytic acid aqueous solution.
[0006] Furthermore, the buffer solution in step (1) is 2 mol / L ammonia.
[0007] Furthermore, the plasma in step (1) is a mixture of argon and oxygen in a volume ratio of 95:5.
[0008] Furthermore, the basalt fiber plain weave fabric mentioned in step (1) has an areal density of 300 g / m². 2 Plain weave fabric of basalt fiber with a single filament diameter of 10μm.
[0009] Furthermore, the silane coupling agent in step (2) is: γ-glycidoxypropyltrimethoxysilane.
[0010] Furthermore, the epoxy resin in step (3) is: bisphenol A type epoxy resin E51.
[0011] Furthermore, the epoxy-modified polyphosphonate oligomer in step (3) is an epoxy-modified polyphosphonate oligomer with a molecular weight of 2000, an epoxy equivalent of 1000 g / eq, and a viscosity (25°C) of 3000 mPa·s.
[0012] Furthermore, the curing agent in step (3) is: methyltetrahydrophthalic anhydride curing agent.
[0013] Furthermore, the accelerator in step (3) is 2,4,6-tris(dimethylaminomethyl)phenol accelerator.
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: This invention utilizes phytic acid, zirconium oxychloride, cerium nitrate, γ-glycidyl etheroxypropyltrimethoxysilane, and epoxy-modified polyphosphonate oligomers through a multi-step process involving low-temperature plasma activation, two-step in-situ coordination deposition, silane gradient grafting, and co-curing with the matrix to achieve excellent aging resistance and superior mechanical properties.
[0015] This invention first employs phytic acid, zirconium oxychloride, cerium nitrate, γ-glycidyl etheroxypropyltrimethoxysilane, and epoxy-modified polyphosphonate oligomers. Through a multi-step process involving low-temperature plasma activation, two-step in-situ coordination deposition, silane gradient grafting, and co-curing with the matrix, an aging-resistant basalt fiber composite material is obtained. By leveraging the strong coordination between the phosphate groups in the zirconium oxychloride hybrid layer and calcium, iron, and magnesium ions on the fiber surface, the ion dissolution channels for catalytic resin hydrolysis are blocked at the source. Simultaneously, a dense barrier layer is formed to inhibit water vapor permeation. Furthermore, the cerium-doped layer utilizes Ce... 3+ / Ce 4+ The reversible valence cycle dynamically captures and quenches free radicals generated by thermo-oxidative and UV aging, interrupting the chain reaction of oxidative degradation. At the same time, the silane gradient transition layer buffers hygrothermal stress and strengthens chemical bonding to prevent debonding. In the matrix, epoxy-modified polyphosphonate oligomers are covalently connected to the resin network and form hydrogen bonds with the interfacial silane, forming a continuous free radical scavenging channel. The above synergy endows the material with excellent aging resistance. One end of the silane gradient transition layer is anchored to the zirconium phytate hybrid layer through condensation, while the epoxy group at the other end participates in resin curing, effectively eliminating stress concentration. Furthermore, the phosphate groups in the zirconium phytate layer chelate microcracks and surface defects on the fiber surface, and cerium doping fills the vacancies in the hybrid network, reducing the weak boundary layer at the interface. Meanwhile, the epoxy-modified polyphosphonate oligomers are covalently connected to the resin network and crosslinked with the silane layer through hydrogen bonds, improving the crosslinking density of the matrix and the interfacial toughness. The synergy of these three factors greatly enhances the interlayer shear strength. Detailed Implementation
[0016] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0017] To more clearly illustrate the method provided by the present invention, the following embodiments are provided in detail. The testing methods for various indicators of the fiber composite materials produced in the following embodiments are as follows: Aging resistance test: The basalt fiber composite materials prepared in Examples 1-5 and Comparative Examples 1-6 were mechanically cut according to the specimen dimensions specified in GB / T3357-2019. The cut surfaces of the specimens were lightly ground with 600-grit sandpaper to remove processing burrs, and placed in a desiccator at room temperature for 24 hours to eliminate residual stress introduced by machining. After being numbered, the initial mass of the specimens was weighed on an analytical balance to an accuracy of 0.1 mg. They were then vertically suspended on the sample rack of a constant temperature and humidity test chamber, with a spacing of not less than 10 mm between the specimens to ensure uniform circulation of the humid and hot atmosphere inside the chamber. The test chamber temperature was set to 85±2℃ and the relative humidity to 85±3%RH. Distilled water or deionized water was used as the humidification medium. The heating rate was set to 2℃ / min. Timing was started after the set temperature and humidity were reached. The total aging period was set to 2000h. The mass of the aged sample was weighed to calculate the water absorption rate. Then, the interlaminar shear strength was determined on a universal testing machine at a loading rate of 1.0mm / min according to the method specified in GB / T 3357—2019. Each group of valid samples should have no less than 6 samples.
[0018] Mechanical property testing: The interlaminar shear strength of the fiber materials prepared in Examples 1-5 and Comparative Examples 1-6 was determined according to GB / T 1450.1-2005. The sample size was 20mm×10mm×2mm, the span-to-thickness ratio was 5:1, and the loading rate was set to 1mm / min. Example 1
[0019] (1) The surface density is 300 g / m 2 Basalt fiber plain weave fabric with a single filament diameter of 10μm was cut into 300mm×300mm specifications and extracted by reflux extraction in a Soxhlet extractor with acetone as solvent for 48h. After extraction, it was dried in a vacuum oven at 100℃ to constant weight. The dried fiber was suspended on a sample holder in a plasma chamber and evacuated to a background vacuum level better than 5Pa. A mixed gas of argon and oxygen with a volume ratio of 95:5 was introduced and the gas flow rate was adjusted to maintain the working pressure at 20Pa. The radio frequency power supply was turned on and the power was set to 100W to perform glow discharge treatment on the fiber for 60s. After the power supply was turned off, dry nitrogen was introduced to restore the atmospheric pressure. The fiber was removed within 30s and became the activated fiber material. High-energy plasma particles bombarded the fiber surface, introducing high-density silanol anchor points into the surface in a controllable manner to avoid lattice damage to the fiber body caused by acid and alkali etching. (2) Mix 50wt% phytic acid aqueous solution with deionized water at a mass ratio of 1:30, stir at 300rpm for 15min at room temperature until fully dissolved, and add 2mol / L ammonia water dropwise to adjust the pH to 4.0 to obtain a mixed solution; separately mix zirconium oxychloride octahydrate with deionized water at a mass ratio of 1:10, stir at 300rpm until clear, and slowly add it to the above mixed solution at a rate of 2 drops / s while continuously stirring. After the addition is complete, continue stirring at room temperature for 30min to obtain a precursor sol. Completely immerse the activated fiber material in the precursor solution and soak at 40℃ for 1h, turning the fiber once every 20min during the period; take out the fiber and rinse it three times with deionized water, and dry it at 80℃ for 30min to obtain intermediate product A; the phytic acid phosphate group forms a strong coordination chelate with iron, calcium and magnesium metal ions on the fiber surface, locking the ion dissolution channel, and at the same time crosslinks with zirconium ions in situ to form a dense organophosphonic acid-zirconium barrier network; (3) Add cerium nitrate hexahydrate to anhydrous ethanol and stir at 300 rpm for 20 min at 25°C until completely dissolved to prepare a 0.01 mol / L cerium nitrate ethanol solution; completely immerse intermediate product A in this solution and soak at 25°C for 1 h to allow Ce to precipitate. 3+ The fiber was anchored to the uncoordinated phosphate / hydroxyl sites remaining in the zirconium phytate framework via coordination; the fiber was removed, washed three times with anhydrous ethanol, and dried at 80°C for 1 h to obtain intermediate product B; Ce 3+ / Ce 4+ Reversible valence state cycling endows the interface with the ability to dynamically capture peroxy radicals and alkoxy radicals, thereby achieving active chemical protection; (4) γ-glycidoxypropyltrimethoxysilane was mixed with a mixed solvent at a mass ratio of 2:100. The mixed solvent was prepared by mixing deionized water and anhydrous ethanol at a volume ratio of 1:9. The pH was adjusted to 4.5 with glacial acetic acid. The mixture was stirred and hydrolyzed at room temperature for 30 min to obtain a silane hydrolysate. The intermediate product B was completely immersed in the hydrolysate and impregnated at 25°C for 30 min. The silanol groups of the silane molecules condensed with the hydroxyl groups on the surface of the hybrid layer to form covalent bonds, and the epoxy end groups were exposed to the outside. The fiber was taken out and rinsed with anhydrous ethanol and pre-cured at 110°C for 15 min to form an intermediate product C with an inorganic-organic gradient transition layer. (5) Mix 90 parts by weight of bisphenol A type epoxy resin E51 and 7 parts by weight of epoxy-modified polyphosphonate oligomer with a molecular weight of 2000, epoxy equivalent of 1000 g / eq, and viscosity (25℃): 3000 mPa·s. Heat to 60℃ and mechanically stir at 300 rpm for 20 min. Then cool to room temperature, add 80 parts by weight of methyltetrahydrophthalic anhydride curing agent and 1 part by weight of 2,4,6-tris(dimethylaminomethyl)phenol accelerator. Continue stirring at room temperature for 15 min at a uniform speed. Degas under a vacuum of -0.095 MPa for 15 min to obtain resin solution. Lay 8 layers of intermediate product C in an orthogonal layup sequence of [0° / 90°]4s. Vacuum to ≤-0.095 MPa and hold for 30 min to check for leaks. Preheat to 60℃ and then guide... The resin solution is poured in, and after the resin completely wets the fiber fabric and flows steadily from the outlet, the injection port and outlet are closed. Gradual curing is carried out at a heating rate of 5℃ / min: the resin is initially gelled at 80℃ for 2 hours to complete the ring-opening reaction of the silane epoxy groups, then the temperature is raised to 120℃ and held for 2 hours to complete the main curing and crosslinking reaction, and finally the temperature is raised to 150℃ and held for 2 hours to achieve deep curing and allow the epoxy groups of the polyphosphonate oligomer to fully participate in the resin network crosslinking. During this process, its phosphate ester groups form an intermolecular hydrogen bond network with the silanol groups of the interfacial silane layer and the hydroxyl groups generated by the epoxy ring opening. The composite material is naturally cooled to room temperature in the furnace, the composite laminate is taken out, and the board is placed in a room temperature desiccator for post-curing treatment for 7 days to release residual thermal stress and stabilize performance, finally obtaining an aging-resistant basalt fiber composite material. Example 2
[0020] (1) The surface density is 300 g / m 2 Basalt fiber plain weave fabric with a single filament diameter of 10μm was cut into 300mm×300mm specifications and extracted by reflux extraction in a Soxhlet extractor with acetone as solvent for 48h. After extraction, it was dried in a vacuum oven at 100℃ to constant weight. The dried fiber was suspended on a sample holder in a plasma chamber and evacuated to a background vacuum level better than 5Pa. A mixed gas of argon and oxygen with a volume ratio of 95:5 was introduced and the gas flow rate was adjusted to maintain the working pressure at 20Pa. The radio frequency power supply was turned on and the power was set to 100W to perform glow discharge treatment on the fiber for 60s. After the power supply was turned off, dry nitrogen was introduced to restore the atmospheric pressure. The fiber was removed within 30s and became the activated fiber material. High-energy plasma particles bombarded the fiber surface, introducing high-density silanol anchor points into the surface in a controllable manner to avoid lattice damage to the fiber body caused by acid and alkali etching. (2) Mix 50wt% phytic acid aqueous solution with deionized water at a mass ratio of 1.2:30, stir at 300rpm for 15min at room temperature until fully dissolved, and add 2mol / L ammonia water dropwise to adjust the pH to 4.1 to obtain a mixed solution; separately mix zirconium oxychloride octahydrate with deionized water at a mass ratio of 1.2:10, stir at 300rpm until clear, and slowly add it to the above mixed solution at a rate of 2 drops / s while continuously stirring. After the addition is complete, continue stirring at room temperature for 30min to obtain a precursor sol. Completely immerse the activated fiber material in the precursor solution and soak at 40℃ for 1.5h, turning the fiber once every 20min during the period; take out the fiber and rinse it three times with deionized water, and dry it at 80℃ for 30min to obtain intermediate product A; the phytic acid phosphate group forms a strong coordination chelate with iron, calcium and magnesium metal ions on the fiber surface, locking the ion dissolution channel, and at the same time crosslinks with zirconium ions in situ to form a dense organophosphonic acid-zirconium barrier network; (3) Add cerium nitrate hexahydrate to anhydrous ethanol and stir at 300 rpm for 20 min at 25°C until completely dissolved to prepare a 0.01 mol / L cerium nitrate ethanol solution; completely immerse intermediate product A in this solution and soak at 25°C for 1.2 h to allow Ce to precipitate. 3+ The fiber was anchored to the uncoordinated phosphate / hydroxyl sites remaining in the zirconium phytate framework via coordination; the fiber was removed, washed three times with anhydrous ethanol, and dried at 80°C for 1 h to obtain intermediate product B; Ce 3+ / Ce 4+ Reversible valence state cycling endows the interface with the ability to dynamically capture peroxy radicals and alkoxy radicals, thereby achieving active chemical protection; (4) γ-glycidoxypropyltrimethoxysilane was mixed with a mixed solvent at a mass ratio of 2:100. The mixed solvent was prepared by mixing deionized water and anhydrous ethanol at a volume ratio of 1:9. The pH was adjusted to 4.6 with glacial acetic acid. The mixture was stirred and hydrolyzed at room temperature for 30 min to obtain a silane hydrolysate. The intermediate product B was completely immersed in the hydrolysate and impregnated at 25°C for 30 min. The silanol groups of the silane molecules condensed with the hydroxyl groups on the surface of the hybrid layer to form covalent bonds, and the epoxy end groups were exposed to the outside. The fiber was taken out and rinsed with anhydrous ethanol and pre-cured at 110°C for 15 min to form an intermediate product C with an inorganic-organic gradient transition layer. (5) Mix 95 parts by weight of bisphenol A type epoxy resin E51 and 7.5 parts by weight of epoxy-modified polyphosphonate oligomer with molecular weight of 2000, epoxy equivalent of 1000 g / eq, and viscosity (25℃): 3000 mPa·s. Heat to 60℃ and mechanically stir at 300 rpm for 20 min. Then cool to room temperature, add 82 parts by weight of methyltetrahydrophthalic anhydride curing agent and 1.2 parts by weight of 2,4,6-tris(dimethylaminomethyl)phenol accelerator, and continue to stir at room temperature for 15 min. Degas under a vacuum of -0.095 MPa for 15 min to obtain resin solution. Lay 8 layers of intermediate product C in an orthogonal layup sequence of [0° / 90°] 4s. Vacuum to ≤-0.095 MPa and hold for 30 min to check for leaks. Preheat to 60℃. Resin solution was then introduced. After the resin completely impregnated the fiber fabric and flowed steadily from the outlet, the injection port and outlet were closed. Gradual curing was carried out at a heating rate of 5℃ / min: the resin was initially gelled at 80℃ for 2 hours to complete the ring-opening reaction of the silane epoxy groups. Then, the temperature was increased to 120℃ and held for 2 hours to complete the main curing and crosslinking reaction. Finally, the temperature was increased to 150℃ and held for 2 hours to achieve deep curing and allow the epoxy groups of the polyphosphonate oligomer to fully participate in the resin network crosslinking. During this process, its phosphate ester groups formed an intermolecular hydrogen bond network with the silanol groups of the interfacial silane layer and the hydroxyl groups generated by the epoxy ring opening. The composite material was naturally cooled to room temperature in the furnace, and the composite laminate was taken out. The board was placed in a room temperature desiccator for post-curing treatment for 7 days to release residual thermal stress and stabilize performance, finally obtaining an aging-resistant basalt fiber composite material. Example 3
[0021] (1) The surface density is 300 g / m 2 Basalt fiber plain weave fabric with a single filament diameter of 10μm was cut into 300mm×300mm specifications and extracted by reflux extraction in a Soxhlet extractor with acetone as solvent for 48h. After extraction, it was dried in a vacuum oven at 100℃ to constant weight. The dried fiber was suspended on a sample holder in a plasma chamber and evacuated to a background vacuum level better than 5Pa. A mixed gas of argon and oxygen with a volume ratio of 95:5 was introduced and the gas flow rate was adjusted to maintain the working pressure at 20Pa. The radio frequency power supply was turned on and the power was set to 100W to perform glow discharge treatment on the fiber for 60s. After the power supply was turned off, dry nitrogen was introduced to restore the atmospheric pressure. The fiber was removed within 30s and became the activated fiber material. High-energy plasma particles bombarded the fiber surface, introducing high-density silanol anchor points into the surface in a controllable manner to avoid lattice damage to the fiber body caused by acid and alkali etching. (2) Mix 50wt% phytic acid aqueous solution with deionized water at a mass ratio of 1.5:30, stir at 300rpm for 15min at room temperature until fully dissolved, and add 2mol / L ammonia water dropwise to adjust the pH to 4.2 to obtain a mixed solution; separately mix zirconium oxychloride octahydrate with deionized water at a mass ratio of 1.5:10, stir at 300rpm until clear, and slowly add it to the above mixed solution at a rate of 2 drops / s while continuously stirring. After the addition is complete, continue stirring at room temperature for 30min to obtain a precursor sol. Completely immerse the activated fiber material in the precursor solution and soak at 40℃ for 2h, turning the fiber once every 20min during the period; take out the fiber and rinse it three times with deionized water, and dry it at 80℃ for 30min to obtain intermediate product A; the phytic acid phosphate group forms a strong coordination chelate with iron, calcium and magnesium metal ions on the fiber surface, locking the ion dissolution channel, and at the same time crosslinks with zirconium ions in situ to form a dense organophosphonic acid-zirconium barrier network; (3) Add cerium nitrate hexahydrate to anhydrous ethanol and stir at 300 rpm for 20 min at 25°C until completely dissolved to prepare a 0.01 mol / L cerium nitrate ethanol solution; completely immerse intermediate product A in this solution and soak at 25°C for 1.5 h to allow Ce to precipitate. 3+ The fiber was anchored to the uncoordinated phosphate / hydroxyl sites remaining in the zirconium phytate framework via coordination; the fiber was removed, washed three times with anhydrous ethanol, and dried at 80°C for 1 h to obtain intermediate product B; Ce 3+ / Ce 4+ Reversible valence state cycling endows the interface with the ability to dynamically capture peroxy radicals and alkoxy radicals, thereby achieving active chemical protection; (4) γ-glycidoxypropyltrimethoxysilane was mixed with a mixed solvent at a mass ratio of 2:100. The mixed solvent was prepared by mixing deionized water and anhydrous ethanol at a volume ratio of 1:9. The pH was adjusted to 4.7 with glacial acetic acid. The mixture was stirred and hydrolyzed at room temperature for 30 min to obtain a silane hydrolysate. The intermediate product B was completely immersed in the hydrolysate and impregnated at 25°C for 30 min. The silanol groups of the silane molecules condensed with the hydroxyl groups on the surface of the hybrid layer to form covalent bonds, and the epoxy end groups were exposed to the outside. The fiber was taken out and rinsed with anhydrous ethanol and pre-cured at 110°C for 15 min to form an intermediate product C with an inorganic-organic gradient transition layer. (5) Mix 100 parts by weight of bisphenol A type epoxy resin E51 and 8 parts by weight of epoxy-modified polyphosphonate oligomer with molecular weight of 2000, epoxy equivalent of 1000 g / eq, and viscosity (25℃): 3000 mPa·s. Heat to 60℃ and mechanically stir at 300 rpm for 20 min. Then cool to room temperature, add 85 parts by weight of methyltetrahydrophthalic anhydride curing agent and 1.5 parts by weight of 2,4,6-tris(dimethylaminomethyl)phenol accelerator, and continue to stir at room temperature for 15 min. Degas under a vacuum of -0.095 MPa for 15 min to obtain resin solution. Lay 8 layers of intermediate product C in an orthogonal layup sequence of [0° / 90°] 4s, evacuate to ≤-0.095 MPa and hold for 30 min to check for leaks, and preheat to 60℃. Resin solution was then introduced. After the resin completely impregnated the fiber fabric and flowed steadily from the outlet, the injection port and outlet were closed. Gradual curing was carried out at a heating rate of 5℃ / min: the resin was initially gelled at 80℃ for 2 hours to complete the ring-opening reaction of the silane epoxy groups. Then, the temperature was increased to 120℃ and held for 2 hours to complete the main curing and crosslinking reaction. Finally, the temperature was increased to 150℃ and held for 2 hours to achieve deep curing and allow the epoxy groups of the polyphosphonate oligomer to fully participate in the resin network crosslinking. During this process, its phosphate ester groups formed an intermolecular hydrogen bond network with the silanol groups of the interfacial silane layer and the hydroxyl groups generated by the epoxy ring opening. The composite material was naturally cooled to room temperature in the furnace, and the composite laminate was taken out. The board was placed in a room temperature desiccator for post-curing treatment for 7 days to release residual thermal stress and stabilize performance, finally obtaining an aging-resistant basalt fiber composite material. Example 4
[0022] (1) The surface density is 300 g / m 2 Basalt fiber plain weave fabric with a single filament diameter of 10μm was cut into 300mm×300mm specifications and extracted by reflux extraction in a Soxhlet extractor with acetone as solvent for 48h. After extraction, it was dried in a vacuum oven at 100℃ to constant weight. The dried fiber was suspended on a sample holder in a plasma chamber and evacuated to a background vacuum level better than 5Pa. A mixed gas of argon and oxygen with a volume ratio of 95:5 was introduced and the gas flow rate was adjusted to maintain the working pressure at 20Pa. The radio frequency power supply was turned on and the power was set to 100W to perform glow discharge treatment on the fiber for 60s. After the power supply was turned off, dry nitrogen was introduced to restore the atmospheric pressure. The fiber was removed within 30s and became the activated fiber material. High-energy plasma particles bombarded the fiber surface, introducing high-density silanol anchor points into the surface in a controllable manner to avoid lattice damage to the fiber body caused by acid and alkali etching. (2) Mix 50wt% phytic acid aqueous solution with deionized water at a mass ratio of 1.8:30, stir at 300rpm for 15min at room temperature until fully dissolved, and add 2mol / L ammonia water dropwise to adjust the pH to 4.4 to obtain a mixed solution; separately mix zirconium oxychloride octahydrate with deionized water at a mass ratio of 1.8:10, stir at 300rpm until clear, and slowly add it to the above mixed solution at a rate of 2 drops / s while continuously stirring. After the addition is complete, continue stirring at room temperature for 30min to obtain a precursor sol. Completely immerse the activated fiber material in the precursor solution and soak at 40℃ for 2.5h, turning the fiber once every 20min during the period; take out the fiber and rinse it three times with deionized water, and dry it at 80℃ for 30min to obtain intermediate product A; the phytic acid phosphate group forms a strong coordination chelate with iron, calcium and magnesium metal ions on the fiber surface, locking the ion dissolution channel, and at the same time crosslinks with zirconium ions in situ to form a dense organophosphonic acid-zirconium barrier network; (3) Add cerium nitrate hexahydrate to anhydrous ethanol and stir at 300 rpm for 20 min at 25°C until completely dissolved to prepare a 0.01 mol / L cerium nitrate ethanol solution; completely immerse intermediate product A in this solution and soak at 25°C for 1.8 h to allow Ce to precipitate. 3+ The fiber was anchored to the uncoordinated phosphate / hydroxyl sites remaining in the zirconium phytate framework via coordination; the fiber was removed, washed three times with anhydrous ethanol, and dried at 80°C for 1 h to obtain intermediate product B; Ce 3+ / Ce 4+ Reversible valence state cycling endows the interface with the ability to dynamically capture peroxy radicals and alkoxy radicals, thereby achieving active chemical protection; (4) γ-glycidoxypropyltrimethoxysilane was mixed with a mixed solvent at a mass ratio of 2:100. The mixed solvent was prepared by mixing deionized water and anhydrous ethanol at a volume ratio of 1:9. The pH was adjusted to 4.8 with glacial acetic acid. The mixture was stirred and hydrolyzed at room temperature for 30 min to obtain a silane hydrolysate. The intermediate product B was completely immersed in the hydrolysate and impregnated at 25°C for 30 min. The silanol groups of the silane molecules condensed with the hydroxyl groups on the surface of the hybrid layer to form covalent bonds, and the epoxy end groups were exposed to the outside. The fiber was taken out and rinsed with anhydrous ethanol and pre-cured at 110°C for 15 min to form an intermediate product C with an inorganic-organic gradient transition layer. (5) Mix 105 parts by weight of bisphenol A type epoxy resin E51 and 8.5 parts by weight of epoxy-modified polyphosphonate oligomer with a molecular weight of 2000, an epoxy equivalent of 1000 g / eq, and a viscosity (25℃) of 3000 mPa·s. Heat to 60℃ and mechanically stir at 300 rpm for 20 min. Then cool to room temperature, add 88 parts by weight of methyltetrahydrophthalic anhydride curing agent and 1.8 parts by weight of 2,4,6-tris(dimethylaminomethyl)phenol accelerator, and continue to stir at a uniform speed for 15 min at room temperature. Degas under a vacuum of -0.095 MPa for 15 min to obtain resin solution. Lay 8 layers of intermediate product C in an orthogonal layup sequence of [0° / 90°] 4s, evacuate to ≤-0.095 MPa and hold for 30 min to check for leaks, and preheat to 60℃. After reaching a certain temperature, resin solution is introduced. Once the resin completely impregnates the fiber fabric and flows steadily from the outlet, the injection and outlet are closed. Gradual curing is then carried out at a heating rate of 5℃ / min: the resin is initially gelled at 80℃ for 2 hours to complete the ring-opening reaction of the silane epoxy groups. Subsequently, the temperature is increased to 120℃ and held for 2 hours to complete the main curing and crosslinking reaction. Finally, the temperature is increased to 150℃ and held for 2 hours to achieve deep curing and allow the epoxy groups of the polyphosphonate oligomer to fully participate in the resin network crosslinking. During this process, its phosphate ester groups form an intermolecular hydrogen bond network with the silanol groups of the interfacial silane layer and the hydroxyl groups generated by the epoxy ring opening. The composite material is then naturally cooled to room temperature in the furnace. The composite laminate is then removed and placed in a room temperature desiccator for post-curing treatment for 7 days to release residual thermal stress and stabilize performance, ultimately obtaining an aging-resistant basalt fiber composite material. Example 5
[0023] (1) The surface density is 300 g / m 2 Basalt fiber plain weave fabric with a single filament diameter of 10μm was cut into 300mm×300mm specifications and extracted by reflux extraction in a Soxhlet extractor with acetone as solvent for 48h. After extraction, it was dried in a vacuum oven at 100℃ to constant weight. The dried fiber was suspended on a sample holder in a plasma chamber and evacuated to a background vacuum level better than 5Pa. A mixed gas of argon and oxygen with a volume ratio of 95:5 was introduced and the gas flow rate was adjusted to maintain the working pressure at 20Pa. The radio frequency power supply was turned on and the power was set to 100W to perform glow discharge treatment on the fiber for 60s. After the power supply was turned off, dry nitrogen was introduced to restore the atmospheric pressure. The fiber was removed within 30s and became the activated fiber material. High-energy plasma particles bombarded the fiber surface, introducing high-density silanol anchor points into the surface in a controllable manner to avoid lattice damage to the fiber body caused by acid and alkali etching. (2) Mix 50wt% phytic acid aqueous solution with deionized water at a mass ratio of 2:30, stir at 300rpm for 15min at room temperature until fully dissolved, and add 2mol / L ammonia water dropwise to adjust the pH to 4.5 to obtain a mixed solution; separately mix zirconium oxychloride octahydrate with deionized water at a mass ratio of 2:10, stir at 300rpm until clear, and slowly add it to the above mixed solution at a rate of 2 drops / s while continuously stirring. After the addition is complete, continue stirring at room temperature for 30min to obtain a precursor sol. Completely immerse the activated fiber material in the precursor solution and soak at 40℃ for 3h, turning the fiber once every 20min during the period; take out the fiber and rinse it three times with deionized water, and dry it at 80℃ for 30min to obtain intermediate product A; the phytic acid phosphate group forms a strong coordination chelate with iron, calcium and magnesium metal ions on the fiber surface, locking the ion dissolution channel, and at the same time crosslinks with zirconium ions in situ to form a dense organophosphonic acid-zirconium barrier network; (3) Add cerium nitrate hexahydrate to anhydrous ethanol and stir at 300 rpm for 20 min at 25°C until completely dissolved to prepare a 0.01 mol / L cerium nitrate ethanol solution; completely immerse intermediate product A in this solution and soak at 25°C for 2 h to allow Ce to precipitate. 3+ The fiber was anchored to the uncoordinated phosphate / hydroxyl sites remaining in the zirconium phytate framework via coordination; the fiber was removed, washed three times with anhydrous ethanol, and dried at 80°C for 1 h to obtain intermediate product B; Ce 3+ / Ce 4+ Reversible valence state cycling endows the interface with the ability to dynamically capture peroxy radicals and alkoxy radicals, thereby achieving active chemical protection; (4) γ-glycidoxypropyltrimethoxysilane was mixed with a mixed solvent at a mass ratio of 2:100. The mixed solvent was prepared by mixing deionized water and anhydrous ethanol at a volume ratio of 1:9. The pH was adjusted to 5.0 with glacial acetic acid. The mixture was stirred and hydrolyzed at room temperature for 30 min to obtain a silane hydrolysate. The intermediate product B was completely immersed in the hydrolysate and impregnated at 25°C for 30 min. The silanol groups of the silane molecules condensed with the hydroxyl groups on the surface of the hybrid layer to form covalent bonds, and the epoxy end groups were exposed to the outside. The fiber was taken out and rinsed with anhydrous ethanol and pre-cured at 110°C for 15 min to form an intermediate product C with an inorganic-organic gradient transition layer. (5) Mix 110 parts by weight of bisphenol A type epoxy resin E51 and 9 parts by weight of epoxy-modified polyphosphonate oligomer with molecular weight of 2000, epoxy equivalent of 1000 g / eq, and viscosity (25℃): 3000 mPa·s. Heat to 60℃ and mechanically stir at 300 rpm for 20 min. Then cool to room temperature, add 90 parts by weight of methyltetrahydrophthalic anhydride curing agent and 2 parts by weight of 2,4,6-tris(dimethylaminomethyl)phenol accelerator. Continue stirring at room temperature for 15 min. Degas under a vacuum of -0.095 MPa for 15 min to obtain resin solution. Lay 8 layers of intermediate product C in an orthogonal layup sequence of [0° / 90°]4s. Vacuum to ≤-0.095 MPa and hold for 30 min to check for leaks. Preheat to 60℃. Resin solution is introduced, and after the resin completely wets the fiber fabric and flows steadily from the outlet, the injection port and outlet are closed. Gradual curing is carried out at a heating rate of 5℃ / min: the resin is initially gelled at 80℃ for 2 hours to complete the ring-opening reaction of the silane epoxy groups, then the temperature is increased to 120℃ and held for 2 hours to complete the main curing and crosslinking reaction, and finally the temperature is increased to 150℃ and held for 2 hours to achieve deep curing and allow the epoxy groups of the polyphosphonate oligomer to fully participate in the resin network crosslinking. During this process, its phosphate ester groups form an intermolecular hydrogen bond network with the silanol groups of the interfacial silane layer and the hydroxyl groups generated by the epoxy ring opening. The composite laminate is naturally cooled to room temperature in the furnace, and the laminate is taken out. The laminate is placed in a room temperature desiccator for post-curing treatment for 7 days to release residual thermal stress and stabilize performance, finally obtaining an aging-resistant basalt fiber composite material.
[0024] Comparative Example 1 The difference between Comparative Example 1 and Example 3 is that step (1) is omitted, and the areal density is 300 g / m³. 2 After the basalt fiber plain weave fabric with a single filament diameter of 10μm was cut into 300mm×300mm specifications, it was added to the precursor solution in step (2) for the experiment. The remaining steps were the same as in Example 3.
[0025] Comparative Example 2 The difference between Comparative Example 2 and Example 3 is that steps (3) and (4) are omitted, and intermediate product A is directly used to replace intermediate product C in the experiment of step (5). The remaining steps are the same as in Example 3.
[0026] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that step (4) is omitted, and intermediate product B is used directly to replace intermediate product C in the experiment of step (5). The remaining steps are the same as in Example 3.
[0027] Comparative Example 4 The difference between Comparative Example 4 and Example 3 is that no epoxy polyphosphonate oligomer is added; the remaining steps are the same as in Example 3.
[0028] Comparative Example 5 The difference between Comparative Example 5 and Example 3 is that step (2) is omitted, and intermediate product A is used instead of intermediate product B in the experimental procedure of step (4). The remaining steps are the same as in Example 3.
[0029] Comparative Example 6 The difference between Comparative Example 6 and Example 3 is that steps (2), (3), and (4) are omitted, and the activated fiber material is used instead of intermediate product C for the experiment in step (5). The remaining steps are the same as in Example 3.
[0030] Example of effect Table 1 below shows the performance analysis results of the fiber composite materials of Examples 1 to 5 and Comparative Examples 1 to 6 of the present invention.
[0031] Table 1
[0032] A comparison of the experimental data on the initial interlaminar shear strength of the embodiments and comparative examples reveals that the present invention first uses phytic acid, zirconium oxychloride, cerium nitrate, γ-glycidyl etheroxypropyltrimethoxysilane, and epoxy-modified polyphosphonate oligomers. Through a multi-step process involving low-temperature plasma activation, two-step in-situ coordination deposition, silane gradient grafting, and co-curing with the matrix, an aging-resistant basalt fiber composite material is obtained. One end of the silane gradient transition layer is anchored to the phytate-zirconium hybrid layer via condensation, while the epoxy groups at the other end participate in resin curing, effectively eliminating stress concentration and significantly improving the interlaminar shear strength. Furthermore, the phosphate groups in the phytate-zirconium layer chelate microcracks on the fiber surface. In addition to addressing surface defects, cerium doping fills vacancies in the hybrid network, reducing weak boundary layers at the interface. Simultaneously, epoxy-modified polyphosphonate oligomers covalently integrate into the resin network and crosslink with the silane layer via hydrogen bonding, increasing the matrix crosslinking density and interfacial toughness. These three factors synergistically significantly enhance interlayer shear strength. Comparison of experimental data from the examples and comparative examples after 2000 hours of damp heat aging reveals that in this invention, the phosphate groups in the zirconium phytate hybrid layer strongly coordinate with calcium, iron, and magnesium ions on the fiber surface, effectively blocking ion dissolution channels that catalyze resin hydrolysis at the source. Simultaneously, a dense barrier layer is formed to inhibit water vapor permeation. Furthermore, the cerium-doped layer, through Ce... 3+ / Ce 4+ The reversible valence cycle dynamically captures and quenches free radicals generated by thermo-oxidative and UV aging, cutting off the chain reaction of oxidative degradation. At the same time, the silane gradient transition layer buffers the damp heat stress and strengthens chemical bonding to prevent debonding. In the matrix, epoxy-modified polyphosphonate oligomers are covalently connected to the resin network and form hydrogen bonds with the interfacial silane, forming a continuous free radical scavenging channel. The above synergy endows the material with excellent aging resistance.
[0033] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No markings in the claims should be construed as limiting the scope of the claims.
Claims
1. A method for preparing an aging-resistant basalt fiber composite material, characterized in that, Includes the following steps: (1) Mix phytic acid solution and deionized water at a mass ratio of 1~2:30, stir at room temperature for 15 min, and add buffer solution to adjust pH to 4.0~4.5 to obtain a mixed solution; mix zirconium oxychloride octahydrate and deionized water at a mass ratio of 1~2:10, stir until clear, and slowly add to the above mixed solution while stirring continuously. Continue stirring for 30 min to obtain a precursor sol. Completely immerse the basalt fiber plain weave fabric that has been pretreated by plasma in the precursor solution, soak at 40℃ for 1~3 h, turn the fiber once every 20 min, take out the fiber, wash, and dry at 80℃ for 30 min to obtain intermediate product A; (2) Add cerium nitrate hexahydrate to anhydrous ethanol and stir at 25°C for 20 min to prepare a 0.01 mol / L cerium nitrate ethanol solution; completely immerse intermediate product A in the solution and soak at 25°C for 1-2 h, remove the fiber, wash it, and dry it at 80°C for 1 h to obtain intermediate product B; completely immerse intermediate product B in silane coupling agent hydrolysate and soak at 25°C for 30 min, remove the fiber, wash it, and pre-cur it at 110°C for 15 min to obtain intermediate product C; (3) Mix 90-110 parts by weight of epoxy resin and 7-9 parts by weight of epoxy-modified polyphosphonate oligomer, heat to 60°C and premix for 20 min, cool to room temperature, add 80-90 parts by weight of curing agent and 1-2 parts by weight of accelerator, continue to stir at a constant speed for 15 min at room temperature, and degas under vacuum for 15 min to obtain resin solution; lay 8 layers of intermediate product C in orthogonal layup sequence, vacuum and pressure test for leaks, preheat to 60°C and then introduce resin solution for gradient curing, cool to room temperature, and place in a room temperature desiccator for curing for 7 days to obtain aging resistant basalt fiber composite material.
2. The aging-resistant basalt fiber composite material according to claim 1, characterized in that, The phytic acid solution in step (1) is a 50wt% phytic acid aqueous solution.
3. The aging-resistant basalt fiber composite material according to claim 1, characterized in that, The buffer solution in step (1) is 2 mol / L ammonia.
4. The aging-resistant basalt fiber composite material according to claim 1, characterized in that, The plasma in step (1) is a mixture of argon and oxygen in a volume ratio of 95:
5.
5. The aging-resistant basalt fiber composite material according to claim 1, characterized in that, The basalt fiber plain weave fabric mentioned in step (1) has an areal density of 300 g / m². 2 Plain weave fabric of basalt fiber with a single filament diameter of 10μm.
6. The aging-resistant basalt fiber composite material according to claim 1, characterized in that, The silane coupling agent in step (2) is γ-glycidoxypropyltrimethoxysilane.
7. The aging-resistant basalt fiber composite material according to claim 1, characterized in that, The epoxy resin mentioned in step (3) is: Bisphenol A type epoxy resin E51.
8. The aging-resistant basalt fiber composite material according to claim 1, characterized in that, The epoxy-modified polyphosphonate oligomer in step (3) is an epoxy-modified polyphosphonate oligomer with a molecular weight of 2000, an epoxy equivalent of 1000 g / eq, and a viscosity (25℃) of 3000 mPa·s.
9. The aging-resistant basalt fiber composite material according to claim 1, characterized in that, The curing agent in step (3) is methyltetrahydrophthalic anhydride curing agent.
10. The aging-resistant basalt fiber composite material according to claim 1, characterized in that, The accelerator mentioned in step (3) is 2,4,6-tris(dimethylaminomethyl)phenol accelerator.
